2015
DOI: 10.2298/pan1501105k
|View full text |Cite
|
Sign up to set email alerts
|

The importance of corporate taxation for FDI attractiveness of southeast European countries

Abstract: The aim of this paper is to research the determinants of FDI inflows in the SEE region with a special emphasis on corporate tax rates. The panel data analysis (GMM methodology) was conducted on six countries in the period 2000-2011 in two versions: as gravity model based on bilateral FDI inflows and on the total FDI inflows (and inward stock). The results pointed the most important determinants for attracting FDI in SEE countries are market size (population), growth rates, GDP per capita, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
2
12
0
1
Order By: Relevance
“…Three of them define taxes as a weak determinant (Bénassy-Quéré et al, 2005;Buettner and Wamser, 2013;Herger et al, 2016). Some four others point to taxes at the same level as other determinants -tax shields, market size, agglomeration effects, public infrastructure (Bénassy-Quéré et al, 2007;Kersan-Škabić, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Three of them define taxes as a weak determinant (Bénassy-Quéré et al, 2005;Buettner and Wamser, 2013;Herger et al, 2016). Some four others point to taxes at the same level as other determinants -tax shields, market size, agglomeration effects, public infrastructure (Bénassy-Quéré et al, 2007;Kersan-Škabić, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kersan-Skabic using data on EU transition economies fails to find evidence that tax rates significantly affect the long-run elasticity of FDI [28]. Studies of Daniels and Egger based on data from the US and other OECD countries basically do not confirm a precise impact of tax rates on the long-run elasticity of foreign investment [29,30].…”
Section: Tax Rates and Foreign Direct Investmentmentioning
confidence: 92%
“…Bannour and Mtar(2015) showed that country size, international trade openness of the economy, infrastructure, geographic proximity, political stability, and skilled human capital are deterministic elements of FDI in Tunisia. Kersan-Skabic (2015) showed that most determinant elements of FDI in southeast European countries are market size, growth rates, GDP per capita, and wages. Padaki and Goel (2015) found that FDI does not provide a relationship on international trade.…”
Section: Fdi and The Channel For International Transmissionmentioning
confidence: 99%